QTL Mapping of Fusarium Ear Rot Resistance in Maize - Wen, Jing (Plant disease, 2021)
Ear rot is a globally prevalent class of disease in maize, of which Fusarium ear rot (FER), caused by the fungal pathogen Fusarium verticillioides, is the most commonly reported. In this study, three F2 populations, namely F2-C, F2-D, and F2-J, and their corresponding F2:3 families were produced by crossing three highly FER-resistant inbred lines, Cheng351, Dan598, and JiV203, with the same susceptible line, ZW18, for quantitative trait locus (QTL) mapping of FER resistance. The individual crop plants were inoculated with a spore suspension of the pathogen injected into the kernels of the maize ears. The broad-sense heritability (H2) for FER resistance was estimated to be as high as 0.76, 0.81, and 0.78 in F2-C, F2-D, and F2-J, respectively, indicating that genetic factors played a key role in the phenotypic variation. We detected a total of 20 FER-resistant QTLs in the three F2 populations, among which QTLs derived from the resistant parent Cheng351, Dan598, and JiV203 explained 62.89 to 82.25%, 43.19 to 61.51%, and 54.70 to 75.77% of the phenotypic variation, respectively. Among all FER-resistant QTLs detected, qRfer1, qRfer10, and qRfer17 accounted for the phenotypic variation as high as 26.58 to 43.36%, 11.76 to 18.02%, and 12.02 to 21.81%, respectively. Furthermore, QTLs mapped in different F2 populations showed some extent of overlaps indicating potential resistance hotspots. The FER-resistant QTLs detected in this study can be explored as useful candidates to improve FER resistance in maize by introducing these QTLs into susceptible maize inbred lines via molecular marker-assisted selection